Novel mutations in the STK11 gene in Thai patients with Peutz-Jeghers syndrome - Ausavarat, Surasawadee (The WJG Press and Baishideng, 2009)
Peutz-Jeghers syndrome (PJS), a rare autosomal dominant inherited disorder, is characterized by hamartomatous gastrointestinal polyps and mucocutaneous pigmentation. Patients with this syndrome have a predisposition to a variety of cancers in multiple organs. Mutations in the serine/threonine kinase 11 (STK11) gene have been identified as a major cause of PJS. Here we present the clinical and molecular findings of two unrelated Thai individuals with PJS. Mutation analysis by Polymerase Chain Reaction-sequencing of the entire coding region of STK11 revealed two potentially pathogenic mutations. One harbored a single nucleotide deletion (c.182delG) in exon 1 resulting in a frameshift leading to premature termination at codon 63 (p.Gly61AlafsX63). The other carried an in-frame 9-base-pair (bp) deletion in exon 7, c.907_915del9 (p.Ile303_Gln305del). Both deletions were de novo and have never been previously described. This study has expanded the genotypic spectrum of the STK11 gene.